Effects of diosmin-hesperidin and low pressure compression stocking combination in superficial venous insufficiency (Annals of Medical Research, 2021)
Aim: The main aim of the study is to investigate the efficacy and patient tolerance of Daflon 1000mg/day and low-pressure compression stocking combination in the treatment of superficial venous insufficiency. Materials and Methods: This prospective study included 112 patients diagnosed with superficial venous insufficiency and reflux in saphenofemoral junction during March 2018 and 2019 at our center. All the patients received 1000 mg micronized purified flavonoid fractions containing 90% diosmin-10% hesperidin and low-pressure venous compression stockings (15-20 mmHg) throughout the study. Patients superficial, perforator, and deep venous systems were evaluated by Doppler US at the beginning and average of 5.3 ± 3.7 months after treatment. Results: A total of 99 (88.4%) patients out of 112 eligible patients completed the investigation. The mean age was 41±12.6, the female was 66 (58.9%), the mean follow-up was 5.3±3.7 months. Pre-treatment and post-treatment diameters of SFJ were 6.27±2.9 and 5.68±1.8 mm, respectively, this was statistically significant (P=0.033). All of the patients have SFJ reflux initially, after the treatment, patients with SFJ reflux were decreased to 44 (44.4%), this was also statistically significant (P0.001, OR:0.004, 95% CI: 0.0002-0.07). We also found significant improvement in grade III and grade IV reflux (P0.05) after treatment. The symptomatic patients decreased from 63 to 16 after treatment, this was statistically severely significant (P0.001, OR:0.11, 95% CI: 0.056-0.216). During the follow-up period, 6 (5.4%) patients were worsened and underwent surgical intervention, this was not statistically significant (P=0.076). Conclusion: Daflon 1000mg/day with a combination of low- pressure CS well tolerates by venous insufficiency patients. Six months of continuous application may reduce the reflux of SFJ and VSM, and causes marked symptomatic relief.
Keywords: Chronic venous insufficiency; diosmin-hesperidin combination; edema